prove that (1-sinA) (tanA+secA)=cosA
Answers
Answered by
2
LHS= (1-sinA) (tanA+secA)
=(1-sinA)(sinA/cosA +1/cosA)
=(1-sinA) (sinA+1/cosA)
=(1+sinA)(1-sinA)/cosA
=1-sin^2 A/cos A
=cos^2A/cos A
=cosA=RHS
PROVED
HOPE IT HELPS
#Nandani
=(1-sinA)(sinA/cosA +1/cosA)
=(1-sinA) (sinA+1/cosA)
=(1+sinA)(1-sinA)/cosA
=1-sin^2 A/cos A
=cos^2A/cos A
=cosA=RHS
PROVED
HOPE IT HELPS
#Nandani
Answered by
2
use trigonometric identities
Attachments:
![](https://hi-static.z-dn.net/files/db4/429b821c2dca54aa3e49c9c66b9e50c0.jpg)
Similar questions